The cybersecurity control playbook : from fundamentals to advanced strategies - Edwards, Jason (Cybersecurity expert) (Wiley, 2025)
"This book is an essential resource for anyone looking to protect their organization in the digital age; whether running a small business, managing a medium-sized company, or leading a large corporation, this book contains strategies that will fit all needs. Written in a highly accessible, jargon-free style, the highly experienced author shares his advice for effective cybersecurity controls which are crucial for protecting sensitive data, maintaining system integrity, and ensuring privacy. They help prevent data breaches, reduce financial risks, and build trust. Additionally, they are vital for meeting regulatory requirements in various industries. As technology advances, these controls will become increasingly important in securing our digital world. Each chapter provides clear explanations of foundational concepts before delving into more advanced topics, ensuring that readers understand the basics. Additionally, the book includes appendices and links to online resources for those who need to brush up on specific skills. By incorporating these supportive elements, the book ensures that all readers can fully grasp and apply the cybersecurity strategies discussed regardless of their starting point"-- Provided by publisher.
Includes index.
Keywords: Computer security.; Data protection.; Business enterprises -- Data processing -- Security measures.; elektronické knihy; electronic books